Lingual Mucosal Lesions for Starting the Secondary Stage of Syphilis: A Case Report - Zhao, Min (Archives of Clinical and Medical Case Reports, 2022)
Background: Recent years syphilis has the increased case rates among men who have sex with men and remains a continuing public health challenge globally. Owing to its varied manifestations of oral mucosa in syphilis that can mimic other infections, it should be distinguished from oral ulcer, candidiasis, oral lichen planus, oral leukoplakia and so on. Case Presentation: This case report describes the patient with white plaques of the lingual mucosa for the secondary stage of syphilis in a 23-year-old male. It was a rare case that oral mucosal lesions as the only manifestations of secondary syphilis. And the differential diagnosis, treatment, follow-up visits and attentions were discussed. Conclusions: The clinicians need to distinguish the oral clinical presentations of syphilis from other oral diseases for suspected syphilis patients and to achieve early diagnosis and treatment. As well do a good job in relevant self-protection, instrument disinfection and management of nosocomial infection.